Soil Contamination and Alternatives for Sustainable Development - Vázquez-Luna, Dinora; del Carmen Cuevas-Díaz, María (IntechOpen, 2019)
The book Soil Contamination and Alternatives for Sustainable Development allows the reader to obtain information about some case studies related to soil contamination, as well as provide sustainable alternatives to reduce environmental damage. The book is divided into two sections, where the first section describes anthropogenic contamination in detail and the second section discusses three alternatives for sustainable development.